2010
DOI: 10.1111/j.1471-8847.2009.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs Assessment in Research Ethics Evaluation Among Research Ethics Committee Members in Three African Countries: Cameroon, Mali and Tanzania

Abstract: Although the majority of REC members in the targeted African countries had received training in ethics, they expressed a need for additional training. The results of this survey have been used to design a training program in research ethics evaluation that meets this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 0 publications
3
36
0
2
Order By: Relevance
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…• necessidades de treinamento • O objetivo de uma ANT é identificar necessidades de treinamento expressas por lacunas de competências que impedem a caracterização de um desempenho no trabalho como excelente nos mais diversos contextos de atuação (Carlisle, Bhanugopan, & Fish, 2011;Trudeau, Ainscough, Trant, Starker, & Cousineau, 2010;Ajjawi, Thistlethwaite, Aslani, & Cooling, 2010;Akhtar-Danesh et al, 2010;Ateudjieu et al, 2010;Cofré et al, 2010).…”
Section: Referencial Teóricounclassified
“…The literature on bioethics in Cameroon has focused primarily on philosophical discussions and opinions [3-9] and the few empirical studies that exist have centered on capacity building of RECs and members of RECs [10-12], while some have discussed ethics and Cameroon journals [13]. Worldwide, studies pertaining to the documentation of ethics approval and informed consent have been dominated by reviews of published journal articles [14-16] and similar studies had been described in Cameroon which reveal that authors of scientific journal articles of research carried out in Cameroon significantly failed to document research ethics approval and informed consent in their publications [17,18].…”
Section: Introductionmentioning
confidence: 99%